2015
DOI: 10.1016/j.ejvs.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Vein Diameter Cannot Be Used as an Indicator of Ovarian Venous Reflux

Abstract: There is no significant difference between the diameters of competent and refluxing ovarian veins and, as such, techniques that measure vein diameter may not be suitable for the diagnosis of venous reflux in the ovarian veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
0
37
1
6
Order By: Relevance
“…17 Slow flow, inflammation, thrombosis, and insufficiency are thought to be responsible for symptom development as pelvic varices can be present in asymptomatic individuals. 7,[22][23][24][25] Factors affecting the diagnosis of PCS include variance of causes and clinical presentations of pelvic pain 1,2,20,26,27 and relatively low sensitivity of noninvasive diagnostic imaging and laparoscopy 6,22 to identify insufficiency compared with catheter venogram. Despite diagnostic challenges, studies show promising results for percutaneous management of PCS delineating it as a treatable syndrome of significant prevalence, morbidity, and systemic costs.…”
mentioning
confidence: 99%
“…17 Slow flow, inflammation, thrombosis, and insufficiency are thought to be responsible for symptom development as pelvic varices can be present in asymptomatic individuals. 7,[22][23][24][25] Factors affecting the diagnosis of PCS include variance of causes and clinical presentations of pelvic pain 1,2,20,26,27 and relatively low sensitivity of noninvasive diagnostic imaging and laparoscopy 6,22 to identify insufficiency compared with catheter venogram. Despite diagnostic challenges, studies show promising results for percutaneous management of PCS delineating it as a treatable syndrome of significant prevalence, morbidity, and systemic costs.…”
mentioning
confidence: 99%
“…Although there are no established criteria for the cross-sectional imaging diagnosis of PCS, relatively arbitrary diagnostic criteria are tortuous and dilated ovarian veins, reflux in ovarian veins, congested parauterine and paraovarian venous plexus, and presence of pelvic varicose veins (11,13,14). Ovarian vein dilatation with diameters greater than 8 mm on the left side and 4 mm on the right side on multidetector computed tomography (MDCT) are defined as clearly abnormal (11), but this diagnostic criterion is not universally accepted (15). There are no cross-sectional imaging studies that reported data regarding to the reference values for ovarian veins size in healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…No symptoms of pelvic congestion syndrome (PCS) were observed in Group 2 patients in spite of the pathological reflux blood flow along the gonadal (25%) and uterine (41.6%) veins. The diameter of intrapelvic veins was ignored, because there was no significant correlation with the presence and severity of VPP as confirmed by previous studies [14,15]. Statistically significant intergroup differences were observed for the laboratory results.…”
Section: Duplex Ultrasonography Datamentioning
confidence: 77%
“…The rea-sons behind the emergence of venous pelvic pain (VPP) remain unclear, and the available hemodynamic and inflammatory hypotheses cannot fully explain what causes the pain syndrome in some patients and why other patients with identical morphofunctional changes in pelvic veins do not have it [11,12,13]. As proved by earlier studies, there is no obvious relationship between the diameter of pelvic veins and the severity of VPP [14,15]. Meanwhile, the findings obtained by several authors indicate that there might be a relationship between neurogenic inflammation, hyperproduction, and increased activity of vasoactive neuropeptides and the emergence of VPP formation [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%